Reflective thinking among life science students in bioentrepreneurship learning: Evidence across four reflective dimensions - Agung Witjoro; Linda Tri Antika; Eka Imbia Agus Diartika; Hadi Suwono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Bioentrepreneurship learning requires life science students to integrate biological knowledge, innovation, sustainability, and entrepreneurial decision-making. Objective: This study examined the reflective thinking profile of life science students in bioentrepreneurship learning. Methods: An explanatory sequential mixed-methods design was employed. Quantitative data were collected from 106 undergraduate students at four Indonesian universities using a questionnaire adapted from Kember et al., followed by semi-structured interviews with five purposively selected students and two lecturers. Quantitative data were analyzed descriptively, while qualitative data were examined thematically. Results: Students showed a high overall level of reflective thinking (M = 76.48; SD = 10.52; mean per item = 3.82). Reflection had the highest score (M = 28.48; mean per item = 4.07), whereas habitual action had the lowest (M = 13.24; mean per item = 3.31). Moreoever, project-based activities, market validation, feedback, and peer–lecturer discussions encouraged evaluation, strategy revision, and broader views of entrepreneurship as innovation and problem-solving. Nevertheless, some students continued to rely on familiar procedures perceived as safer. Conclusion: Bioentrepreneurship learning supports reflection-on-action and perspective transformation, but structured reflection before, during, and after projects is needed to reduce habitual responses and strengthen adaptive decision-making.